Pengaruh Omnichannel Marketing dan Product Assortment terhadap Minat Beli Konsumen Evolene : (Studi pada Konsumen Evolene di Kota Medan) (International Forum of Researchers and Lecturers, 2025)
Exercise is an essential activity for maintaining physical fitness and has driven the growing demand for fitness supplements. Evolene, as one of the leading supplement brands in Indonesia, implements Omnichannel Marketing and Product Assortment strategies to expand its market reach. This study aims to analyze the influence of these two strategies on consumer purchase intention toward Evolene in Medan City. The research employed an associative quantitative approach with questionnaires as the primary instrument, and the data were analyzed using multiple linear regression with t-test, F-test, and coefficient of determination. The findings indicate that both Omnichannel Marketing and Product Assortment have a positive and significant effect on purchase intention, both partially and simultaneously, contributing 55% to purchase intention, while the remaining 45% is explained by other factors beyond this study. In conclusion, consumer purchase intention is largely determined by the consistency of omnichannel strategies and the diversity of product offerings. The practical implication suggests the need for enhanced synchronization of cross-channel marketing content and deeper product assortment development to address the diverse needs of consumers.